2008
DOI: 10.1074/jbc.m801839200
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Synthesis of Cysteinyl-tRNACys in Methanosarcina mazei

Abstract: mazei CysRS and SepRS reveals that each enzyme prefers a distinct tRNACys isoacceptor or pair of isoacceptors. Recognition determinants distinguishing the tRNAs are shown to reside in the globular core of the molecule. Both enzymes also require the S-adenosylmethionedependent formation of m1 G37 in the anticodon loop for efficient aminoacylation. We further report a new, highly sensitive assay to measure the activity of SepCysS under anaerobic conditions. With this approach, we demonstrate that SepCysS functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…Although a S 2Ϫ equivalent is likely a sulfur donor for the persulfidation of SepCysS (described above), the low in vitro sulfhydrylation activity of SepCysS with sodium sulfide suggested that bisulfide is unlikely to be the physiological sulfur donor (2,8). Because SepCysS was able to receive sulfur from the IscS persulfide, an unidentified protein-carrying persulfide possibly provides the sulfur for the persulfidation of SepCysS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a S 2Ϫ equivalent is likely a sulfur donor for the persulfidation of SepCysS (described above), the low in vitro sulfhydrylation activity of SepCysS with sodium sulfide suggested that bisulfide is unlikely to be the physiological sulfur donor (2,8). Because SepCysS was able to receive sulfur from the IscS persulfide, an unidentified protein-carrying persulfide possibly provides the sulfur for the persulfidation of SepCysS.…”
Section: Discussionmentioning
confidence: 99%
“…6). This reaction scheme can also explain the in vitro activity with sulfide, which may directly attack the disulfide of SepCysS or the double bond of the dehydroalanyl moiety (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, formation of this complex caused both SepRS and SepCysS to dissociate from their oligomeric states into monomers (15), and thus this complex is unlikely to be physiologically active. Furthermore, addition of SepRS to the SepCysS reaction does not improve CystRNA Cys production (16). Here we present a translation factor, SepCysE, essential for tRNA-dependent Cys biosynthesis in methanococci.…”
mentioning
confidence: 88%
“…All steps of the Cys-tRNA Cys formation were performed in an anaerobic chamber with an atmosphere of 95% (vol/vol) N 2 and 5% (vol/vol) H 2 . The assay used 1 mM Na 2 S as the sulfur donor and was carried out as described (16) with modification (SI Materials and Methods).…”
Section: Measurement Of Cys-trnamentioning
confidence: 99%
“…Other pattern 8 genes that may be involved in OM synthesis and calcification include zinc metalloproteinase nas-13 (CAON980 -an astacin-like metalloproteinase) and cysteinyl-tRNA synthetase (AOSC1122). Nas-13 belongs to a family of metalloproteinases involved in bone growth and morphogenesis (Xiong et al, 2006), and cysteinyltRNA synthetase regulates cysteine (cys) metabolism and protein synthesis (Hauenstein and Perona, 2008). Cys residues are common in many types of extracellular matrix proteins Pearsall et al, 2002) since disulfide bonds act to create a structural framework.…”
Section: Polyp-specific Processesmentioning
confidence: 99%